PENGEMBANGAN LEMBAR AKTVITAS SISWA BERBASIS BUDAYA MANDAILING UNTUK MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIS SISWA - Nadrah Afiati Nasution (Universitas Samudra, 2022)
This study aims to analyze: 1) the effectiveness of the Mandailing culture-based Student Activity Sheet developed on students' mathematical reasoning abilities; 2) improving students' mathematical reasoning skills using the developed Student Activity Sheet. This research is a development research using the Thiagarajan, Semmel, and Semmel learning device development model, namely the 4-D Model which consists of four stages, namely the define, design, develop and disseminate stages. In general, the research process was carried out in two stages, namely the first stage of developing the Mandailing culture-based Student Activity Sheet using the 4-D development model, and the second stage testing the developed Student Activity Sheet. The subjects in this study were students of class XI SMK Sandhy Putra 2 Medan, while the object in this study was the Student Activity Sheet (LAS) based on Mandailing culture on transformation material. in terms of: a) classical completeness; b) achievement of learning objectives; and c) the achievement of learning time, and 2) the improvement of students' mathematical reasoning abilities by using the culture-based Student Activity Sheet that was developed